Examining pathogen avoidance in predator-prey and scavenging systems - Clapp, Justin G.; Malmberg, Jennifer L.; Holbrook, Joseph D. (Frontiers in Ecology and Evolution, 2024)
That predators ‘cull the sick and the weak’ is an adage in ecological texts, but the mechanisms by which disease is curtailed within ecosystems has puzzled ecologists for many years. Advances in our understanding of host-pathogen interactions have revealed defense mechanisms implemented by hosts that minimize infectious diseases in wild populations. Defense mechanisms for hosts include adaptations that ameliorate fitness loss or preemptively limit pathogen exposure, and these mechanisms underlie fundamental questions about how scavenging or predation influence pathogen transmission. A key lens for our understanding of predator-prey and scavenging dynamics include behaviorally-mediated trade-offs weighed by consumers between nutritional gains and pathogen exposure risks. Consequently, the degree to which pathogens and associated diseases perpetuate through food webs can be partly attributed to behavioral responses of predators and scavengers, particularly their selection or avoidance of diseased prey and infected carcasses. Even so, examinations of avoidance or preference by predators and scavengers to diseased carrion are underrepresented. Here we identify areas for future research focused on behavioral immunity that could illuminate where, when, and how pathogen transmission reverberates through ecological communities. While directly attributing behavioral responses to pathogen exposure may be challenging, particularly for organisms with low susceptibility to spillover, identifying these responses though experimentation or observation help describe complex systems regarding infectious disease.